Мирмекофауна (Hymenoptera, Formicidae) степных заповедников Украины: зоогеографические аспекты - Хоменко, В.Н.; Радченко, А.Г.; Макаревич О.Н. (Вестник зоологии, 2008)
Обобщены данные по мирмекофауне шести степных заповедников Украины, где обнаружено 50 видов муравьев из 17 родов. Проанализировано соотношение видового богатства, зоогеографических и экологических элементов, а также рассмотрена взаимосвязь фаун исследованных территорий. Сделано предположение об «эталонном», наиболее типичном для современных степных экосистем Украины, характере мирмекофауны заповедника «Хомутовская Степь». Data on the ant fauna of six steppe natural reserves of Ukraine are summarised. Totally, 50 ant species of 17 genera were found on these territories. Correlations of the species richness with zoogeographic and ecological elements are analyzed, and differences in the myrmecofauna of the studied areas are considered. It is suggested that the ant fauna of the Khomutovsky Step Natural Reserve is the most typical among those of modern steppe ecosystems of Ukraine.